Learning Burnout; Teacher's Strategy in Creating Effective Learning - Sabran Sabran; Riswadi Riswadi; Hasan Baharun; Siti Nur Hidayah; Siti Aminah (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Learning burnout must get serious attention from the teacher so that the learning he does becomes effective and efficient. This study aims to discover the strategies used to overcome learning saturation for early childhood at school. This type of research uses a qualitative case study approach, an inquiry method that emphasizes the search for meaning, understanding, concepts, characteristics, symptoms, symbols or descriptions of a phenomenon in the research setting, prioritizing quality, using several methods, and presenting narratively. Data collection techniques were carried out through interviews, observation and documentation. The data analysis technique was carried out through three stages: data reduction, data presentation, and conclusion drawing. The research and discussion results show that strategies for overcoming learning saturation in early childhood have been carried out very well and optimally. The use of methods, media, learning strategies and interactions with students is planned and systematic to reduce learning boredom in the classroom.